EPISTIMOLOGI PENDIDIKAN ISLAM (Suatu Kajian Tentang Toleransi Dalam Perspektif Epistemologi Pluralistik) - Bahrullah, Bahrullah; Rijal, Syamsul; M. Yunus, Firdaus (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2025)
Education should be a tool to respect human dignity, prepare individuals to be able to live in this world and interact with others, education cannot be understood in one single interpretation. Therefore, Islamic education has an important role in supporting or even threatening plurality, ethnic, religious and cultural diversity in Indonesia. Pluralistic epistemology is a view that emphasizes the value of tolerance towards differences and diversity. Pluralistic epistemology assumes that there is no one approach that can explain everything, and there is no single source of truth that can be used as a benchmark. Pluralistic epistemology emphasizes the importance of accepting and respecting the differences and diversity of perspectives that exist in society. This research is a study of the epistemology of Islamic education which aims to discuss tolerance from a pluralistic epistemological perspective. This research was carried out with a descriptive approach through a literature review or theoretical study by studying journals or books related to the epistemology of Islamic education, while data analysis was carried out using the content analysis method. The results of this research show that tolerance in a pluralistic epistemological perspective emphasizes the importance of respecting diversity of views and different ways of understanding truth. According to the pluralistic epistemological approach, there are various methods for obtaining truth and knowledge. In this context, tolerance does not only mean respecting differences, but also openness to listening, understanding and respecting various existing views, whether in the realm of religion, culture or belief. In education, the application of pluralistic epistemology has a significant impact on the development of inclusive attitudes, mutual respect and a deep understanding of diversity. With this approach, Islamic religious education, for example, can become more open and less dogmatic, providing space for students to develop a broader understanding of various religious and cultural perspectives. This also contributes to the creation of a more tolerant, harmonious society, and is able to reduce potential social conflicts originating from differences in beliefs and traditions. However, it is important to remember that although pluralistic epistemology values multiple perspectives, the non-negotiable basic principles of religion must still be maintained.